(untitled) (Vallis Aurea, 2023)
The correct settlement of a property taxation system is a topic of interest at the moment, which draws attention in economic or academic debates. One of the most convenient alternatives and easier to implement in order to raise revenues to the state budgetis the taxation of property. The comparative analysis of property tax systems in the European Union reveals the need to develop and modernize the property tax system in the new member countries. The tax paid by taxpayers who own property is considered thetax with the fewest negative effects on economic growth, given the immobility of the subject of taxation. This reduces the behavioural effects of this type of tax and minimizes economic distortions. For this reason, is considered necessary to be presented the recent European perspective regarding the taxation of property, be it buildings for housing or special purpose, owned by individuals or corporate. In these conditions, the paper aims to analyze the correlation between the purchasing power of citizens of EU28 countries and the level of property taxes and to perform a grouping of European Union countries according to these indicators. The findings can help governments of the new member countries of European Union to develop a property tax system that would lead to the economic development.